Psychological factors of students’ self-regulation in the process of socialization - Shavyro, A. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
Іn the articleis analyzed theoretically andis exploredempirically the psychological features of self-regulation of conduct of students. In the article is presented the results of the expert poll of teachers of higher educational institutions.